The Evaluation of the Implementation of Boundary System in B2B Relations with Suppliers (Case Study: A Retail Grocery, PT. X) - Maria Kiftya, Ananda; Bachtiar, Emil (Jurnal Manajemen dan Organisasi, 2023)
The purpose of this research is to evaluate the implementation of the boundary system in an effort to better business to business (B2B) relations than the retail company PT. X to suppliers who conform to the concept of levers of control with the support of existing compliance programs in the company. Within the levers of control, the boundary system is a control strategy to determine the company's competitive position. This study used a qualitative methodology, which was designed as an intensive case study involving several methods of data collection and analysis including interviews, field observations and document analysis. The results of this study indicate the ineffectiveness of the boundary system in management support in the implementation of the boundary system, the application of business conduct boundaries, and the implementation of government regulations even though the compliance program in the PT. X company has been effective, causing the main dimensions of successful collaboration in business relations with suppliers to not be achieved.